The Community-Based Ecotourism Development Strategy of The Mataram Cultural Tourism Area of Mangunan Forest Management Resort - Nur Wahidatul Muflihah; Sucihatiningsih Dian Wisika Prajanti (Komunitas, 2023)
This study aims to develop Community Based Ecotourism Development Strategies for the Mataram Cultural Tourism Area of Mangunan Forest Management Resort. The analytical methods used in this study include Fishbone diagrams, qualitative data analysis, and analytical Hierarchy Process (AHP). The result shows that the Mataram Cultural Tourism still has several obstacles in some aspects, which include human resource aspects, institutional aspects, marketing aspects, infrastructure aspects, attractions, and competitiveness. Even though there are still various obstacles and problems, the Mataram Cultural Tourism also has a lot of cultural-based potentials such as the Cultural Show of Mataram Cultural Tourism with a series of kenduri activities, cultural carnivals, dance performances, and dance performances that tell about the history and myths of the Mangunan people. The supporting variables for the development of the Mataram Cultural Tourism Area include supporting facilities and attractions including parking lots, food stalls, photo spots, prayer rooms, bathrooms, and camping areas. The criteria that are most prioritized in the community-based ecotourism development strategy of Mataram cultural tourism area of Mangunan Forest Management Resort are infrastructure criteria with a weight value of 43.9%. Meanwhile, the most prioritized alternative is the addition of supporting facilities for tourism objects in the form of tourist shopping places (restaurants and gift shops) by the community with a weight value of 21.2%. A suggestion that can be conveyed in this research is the government in this case the local tourism office must continue to assist optimally and sustainably so that Mataram Cultural Tourism Area can continue to grow and is increasingly in demand by the public. This research still has limitations on the focus of the object, which is still limited so further research can expand the tourism object to be more comprehensive.